Y = a (x + 3)² - 1
Let's take the point (-1;3)
3 = a ( -1 + 3)² - 1
3 = 4a - 1
4a = 4
Therefore a = 4/4 = 1
(x+3)² - 1
= x² + 6x + 9 - 1
= x² + 6x + 8
The answer would be y = x² + 6x + 8.
Hope this helps !
Photon
2x - 3y = 6
-3y = 6 - 2x
y = -2 + 2/3x
The answer to this question is 2 because 3-3=0×6=0+2=2
Answer:
y = 4x + 4
Step-by-step explanation:
Two points you can see on the graph are (0,4) and (-2,-4)
Now, to find the slope, use delta y/ delta x
(-4-4)/(-2-0)
(-8)/(-2) = 4
Slope is 4.
y = 4x + b
Now, to find b, we need the y-intercept, which is the point where x is 0 and the graph crosses the y-axis.
This value is 4. So, the y-intercept is 4
Substitute into your equation
y = 4x + 4